Evaluation of Rheological Properties and Swelling Behaviour of Sonicated Scleroglucan Samples - Siddique Akber Ansari; Tommasina Coviello; Franco Alhaique; Chiara Di Meo; Pietro Matricardi (Molecules, 2012)
Scleroglucan is a natural polysaccharide that has been proposed for various applications. However there is no investigation on its property variations when the molecular weight of this polymer is reduced. Scleroglucan was sonicated at two different polymer concentrations for different periods of time and the effect of sonication was investigated with respect to molecular weight variations and rheological properties. Molar mass, estimated by viscometric measurements, was drastically reduced already after a sonication for a few min. Sonicated samples were used for the preparation of gels in the presence of borate ions. The effect of borax on the new samples was investigated by recording the mechanical spectra and the flow curves. A comparison with the system prepared with the dialysed polymer was also carried out. The anisotropic elongation, observed with tablets of scleroglucan and borax, was remarkably reduced when the sonicated samples were used for the preparation of the gels.